Rare Case of Renal-type Clear Cell Carcinoma of the Prostate and Review of the Literature - HAN, SONG IY (In Vivo, 2020)
Background/Aim: Renal-type clear cell carcinoma (RTCCC) occurring as a primary tumor in an extra- renal location, especially in the prostate, is very rare. In this report, we present a rare case of RTCCC of the prostate and review the current literature on this condition. Case Report: The patient was a 76-year-old man who presented with urinary symptoms. Cystoscopic findings showed tumor-like lesions in the dome, neck, and anterior wall of the urinary bladder. Biopsy revealed clear cell carcinoma (CCC). Transrectal needle biopsy of the prostate revealed prostatic adenocarcinoma with CCC features. Immunohistochemically, tumor cells of the bladder and prostate were compatible with prostatic carcinoma. The whole-body radiologic workup did not reveal any renal or other organ malignancies. Transurethral resection of the prostate and bladder tumor was performed. The patient underwent regular follow-up cystoscopic examination and urine cytology. No recurrence was observed 19 months after the diagnosis. Conclusion: This was a case of RTCCC arising in the prostate. RTCCC of the prostate is extremely rare and shows very similar histological and immunohistochemical features to those of CCC occurring in the kidney. Pathologists should be aware of such an entity whenever they see clear cells in urinary tract malignancies.